How smallholder farmers adapt to climate change: Stories from East Africa—Emily Marigu Ireri - Ireri, E.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2010)
Oh how sweet those potatoes can be! Faced with a changing climate, Kenyan farmer Emily Marigu Ireri diversified her crops to drive away hunger and poverty. Instead of only growing maize and beans in her farm, she now also plants sweet potatoes, regular potatoes and cassava. The sweet potatoes are now even more important to her than the regular crops maize and beans. The rainfall pattern is changing, and she changes with it, in order to sustain herself, her family and the farm (Emily Marigu Ireri—Kiaragana Village Njeru-ri, Kenya)